Restrictions on Freedom of Religion in the Time of National Disaster—Lessons from Mohamed and Others v President of the Republic of South Africa and Others - Dube, Angelo (South African Yearbook of International Law)
In late 2019, reports of a novel influenza-like virus emerged from China, whose Province of Wuhan was severely affected. It was not until February 2020 that the World Health Organisation was able to give this virus the name Covid-19. At that stage, the world was clearly dealing with a pandemic. Governments worldwide, including the South African government, responded by declaring a state of disaster and imposing restrictions on travelling and public assemblies. After declaring a state of disaster, the government promulgated the lockdown regulations, which prohibited, amongst others, congregating for religious purposes. A group of adherents of the Islamic faith felt aggrieved by these regulations, alleging that they were irrational and unreasonable, to the extent that they unfairly limited their freedom of movement and religion. They launched a constitutional challenge in the High Court in the case of Mohamed and Others v President of the Republic of South Africa and Others. In casu, the court had to deal with the novel issue of the limitation of rights in the context of a pandemic, as well as the rights of religious minorities.